Screening post-menopausal women for bone mineral level by bioelectrical impedance spectroscopy of dominant arm - Öztürk, Nermin. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2018., 2018)
Dominant arm bioimpedance spectroscopy (BIS) and lumbar and hip dual energy x-ray absorptiometry (DXA) measurements were conducted simultaneously on 48 post - menopausal women, aged between 43 and 86 years, with no hip or arm fracture history at Department of Radiology of Istanbul University Cerrahpaşa Hospital. According to lumbar DXA results, 21 women were classiﬁed as normal, 22 as osteopenia and 5 as osteoporosis; whereas hip DXA results classiﬁed 30 women as normal, 15 as osteopenia and 3 as osteoporosis. Only 26 participants had identical lumbar and hip BMD diagnostic results. Dominant arm characteristic frequencies of normal subjects were signiﬁcantly diﬀerent from osteoporotic subjects based on both lumbar (p < 0.005) and hip classiﬁcation groups (p < 0.001). Hip and lumbar spine DXA BMD values were signiﬁcantly correlated (r = 0.55, p < 0.005). The dominant arm BIS characteristic frequency, considered as the one of the single predictors in earlier diagnosis of osteoporosis, was found negatively correlated with DXA measurements for both hip and lumbar spine regions. The Spearman rank correlation coeﬃcient of BIS values with the hip DXA values (r = -0.53, p < 0.001) was higher than that of lumbar spine(r=-0.37, p<0.001). Inreceiveroperatingcharacteristic(ROC)curveanalysis, the best discrimination of dominant arm characteristic frequency was made between normalandosteoporoticsubjectsbasedonthehipsubgroups(p<0.001). Bothlumbar bone mineral content (BMC) (r = -0.47, p < 0.001) and hip BMC (r = -0.4340, p < 0.005) were signiﬁcantly correlated with dominant arm characteristic frequency.|Keywords : bioimpedance spectroscopy, bone mineral content, osteoporosis, osteopenia, bone mineral density, dual energy x - ray absorptiometry.
Keywords: Menopause.; X-ray spectroscopy.; Osteoporosis.